Between DSM and ICD: Paraphilias and the Transformation of Sexual Norms - Giami, Alain (Archives of sexual behavior, 2015)
The simultaneous revision of the two major international classifications of disease, the Diagnostic and Statistical Manual of Mental Disorders and the International Classification of Diseases , serves as an opportunity to observe the dynamic processes through which social norms of sexuality are constructed and are subject to change in relation to social, political, and historical context. This article argues that the classifications of sexual disorders, which define pathological aspects of “sexually arousing fantasies, sexual urges or behaviors” are representations of contemporary sexual norms, gender identifications, and gender relations. It aims to demonstrate how changes in the medical treatment of sexual perversions/paraphilias passed, over the course of the 20th century, from a model of pathologization (and sometimes criminalization) of non-reproductive sexual behaviors to a model that reflects and privileges sexual well-being and responsibility, and pathologizes the absence or the limitation of consent in sexual relations.